Military camouflage coating and preparation method thereof

By using modified Fe3O4@ZIF-8, manganese, aluminum, boron MAB phase ceramic materials and other components in military stealth coatings, the problems of insufficient response, poor chemical stability and short service life of existing coatings in multi-detection methods have been solved, and the multi-band stealth and chemical stability have been improved.

CN119842302AActive Publication Date: 2025-04-18XIAMEN JINSHANG RESIN CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510149484.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-18
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing military stealth coatings have insufficient stealth performance when facing a variety of detection methods, poor chemical stability and short service life.

Method used

The modified Fe3O4@ZIF-8, manganese aluminum-boron MAB phase ceramic materials, carbon nanotubes, nano zinc oxide, nanotitanium dioxide and isomyl p-methoxycinnamic acid are used in combination in a specific proportion to form a coating to meet the stealth needs of radar, infrared, laser and other detection methods, and improve chemical stability.

Benefits of technology

It achieves all-round stealth of a variety of detection methods, extends service life, improves chemical stability, and ensures performance maintenance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005267597850000141
    Figure BDA0005267597850000141
Patent Text Reader

Abstract

The invention relates to military camouflage paint and a preparation method thereof, belongs to the technical field of paint, and aims to solve the problems of insufficient coping with multiple detection means, poor chemical stability and short service life of existing camouflage paint for clothes or tents. A modified Fe3O4-ZIF-8, a manganese-aluminum-boron MAB phase ceramic material, carbon nanotubes, nano zinc oxide, nano titanium dioxide, isoamyl p-methoxycinnamate and other components are matched for use according to a specific proportion, so that the coating can meet the stealth requirements of radar, infrared, laser and other detection means at the same time, has good chemical stability, and can be widely applied to the field of stealth of various detection means. And the service life can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a military stealth coating and a preparation method thereof. Background Art

[0002] The traditional military combat environment is relatively simple, and the army's concealment needs for equipment are mainly focused on visual camouflage. However, with the rapid development of modern detection technology, such as the widespread application of radar detection, infrared detection, and multi-spectral detection, simple visual camouflage alone can no longer meet battlefield needs. The enemy can easily find the army's traces through the reflection of radar waves, the infrared radiation emitted by objects, and the characteristic differences under different spectra. Therefore, the stealth coating technology for military clothing and tents came into being, aiming to comprehensively counter a variety of detection methods and ensure the concealment of military operations.

[0003] In terms of radar stealth, the stealth coatings of military clothing and tents need to effectively absorb or scatter radar waves. Materials with special electromagnetic properties are usually added to the coatings, such as conductive polymers, metal powders, and ceramic materials. Conductive polymers can interact with radar waves with their unique conjugated structure, converting electromagnetic energy into heat energy for consumption; metal powders reflect and scatter radar waves through their own conductivity and magnetism, interfering with normal radar detection. These materials are combined in specific proportions and microstructures, so that the stealth coating has good wave absorption performance in the radar frequency band, effectively reducing the echo signal strength of clothing and tents on the radar screen, making it difficult for enemy radars to detect targets.

[0004] For infrared detection, stealth coatings achieve stealth effects by adjusting the infrared emissivity of the coating. Infrared detection equipment mainly captures the difference in infrared radiation emitted by objects to identify targets. The stealth coatings of military clothing and tents use materials with low infrared emissivity, such as metal oxides doped with specific elements. These materials can reduce the infrared radiation intensity on the surface of the equipment, making it similar to the infrared characteristics of the surrounding environment, making it difficult to be distinguished by infrared detection equipment. In addition, some coatings also have thermal management functions, which can effectively adjust the temperature distribution on the surface of the equipment, avoid the formation of obvious hot spots on the surface of clothing and tents due to the heat generated by personnel activities or equipment operation, and further enhance the infrared stealth performance.

[0005] Early stealth coating technology had many limitations, such as single function, only able to cope with a certain detection method; short service life, easy to fail in harsh outdoor environments; and complex coating process and high cost. With the continuous advancement of materials science and nanotechnology, new stealth coatings continue to emerge. The application of nanomaterials has brought a qualitative leap in stealth coatings. Nanoscale particles have special surface effects and quantum size effects, which can significantly improve the performance of coatings. For example, adding nanoscale carbon tubes, graphene and other materials to coatings not only enhances the coating's ability to absorb electromagnetic waves in different bands, achieving broadband stealth, but also improves the coating's wear resistance and chemical stability, extending the service life of clothing and tents.

[0006] Although the stealth coatings for military clothing or tents have made some progress, they still have the following problems and defects:

[0007] (1) Insufficient response to multiple detection methods: It is difficult to simultaneously meet the stealth requirements of multiple detection methods such as radar, infrared, and laser, and it is often difficult to focus on one while neglecting another.

[0008] (2) Some special materials used in stealth coatings have poor chemical stability and are easily reacted with oxygen, moisture, etc. in the air, which reduces the stealth performance and may affect the service life of clothing or tents.

[0009] Therefore, it is necessary to continuously improve coating technology to overcome various usage defects and ensure stealth safety and service life. Summary of the invention

[0010] In view of the problems of insufficient response to multiple detection means, poor chemical stability and short service life of the stealth coatings of existing clothing or tents, the present invention provides a military stealth coating and a preparation method thereof, which adopts modified Fe3O4@ZIF-8, manganese aluminum boron MAB phase ceramic materials, carbon nanotubes, nano zinc oxide, nano titanium dioxide, isoamyl p-methoxycinnamate and other ingredients, and uses them in a specific proportion, so that the coating can simultaneously meet the stealth requirements of multiple detection means such as radar, infrared, laser, etc., and has good chemical stability, which can effectively extend the service life. Its specific technical scheme is as follows:

[0011] A military stealth coating, the coating comprising the following raw materials in parts by weight: 4 to 6 parts of modified Fe3O4@ZIF-8, 12 to 15 parts of manganese aluminum boron MAB phase ceramic material, 6 to 8 parts of carbon nanotubes, 2 to 3 parts of nano zinc oxide, 2 to 3 parts of nano titanium dioxide, 2 to 3 parts of isopentyl p-methoxycinnamate, 3 to 4 parts of silane coupling agent KH-560, 50 to 60 parts of polyurethane resin, 1 to 1.5 parts of polycarboxylate dispersant and 6 to 8 parts of isocyanate crosslinking agent, 0.5 to 1 part of acetylene glycol wetting agent, 0.2 to 0.5 parts of silicone defoamer, 3 to 5 parts of phosphate plasticizer and 35 to 45 parts of solvent;

[0012] The modified Fe3O4@ZIF-8 is Fe3O4@ZIF-8 surface-modified by aminopropyltriethoxysilane.

[0013] In the above-mentioned coating, the preparation method of the modified Fe3O4@ZIF-8 comprises the following steps: according to the mass ratio, Fe3O4@ZIF-8:aminopropyltriethoxysilane=100:(2-5), Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 6 to 8 times of Fe3O4@ZIF-8 at 40kHz to 60kHz until uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the mixture is stirred at 60°C to 80°C at a speed of 200r / min to 400r / min for reaction. The mixture should be centrifuged at a speed of 8000 r / min to 10000 r / min for 15 min to 25 min for 3 h to 5 h, the supernatant should be discarded, the precipitate should be washed 1 to 2 times with toluene (1.8 to 2.5 times the mass of the precipitate), and then washed 2 to 3 times with ethanol (1.8 to 2.5 times the mass of the precipitate), and then dried in a vacuum drying oven at 55°C to 65°C for 12 h to 15 h, and broken up to obtain Fe3O4@ZIF-8 surface-modified with aminopropyltriethoxysilane, i.e., modified Fe3O4@ZIF-8.

[0014] In the above-mentioned preparation method of modified Fe3O4@ZIF-8, the particle size range of the Fe3O4@ZIF-8 is 150nm to 400nm.

[0015] In the above coating, the solvent includes the following raw materials in parts by mass: 40 to 50 parts of deionized water, 20 to 40 parts of propylene glycol methyl ether, 10 to 30 parts of propylene glycol methyl ether acetate and 10 to 25 parts of dipropylene glycol dimethyl ether.

[0016] In the above coating, the sheet diameter of the manganese aluminum boron MAB phase ceramic material ranges from 5 μm to 50 μm.

[0017] In the above coating, the particle size of the carbon nanotubes is below 30 nm.

[0018] In the above coating, the particle size of the nano zinc oxide is below 30 nm.

[0019] In the above coating, the particle size range of the nano titanium dioxide is below 50 nm.

[0020] The preparation method of the above-mentioned military stealth coating comprises the following steps:

[0021] S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain a mixture A; add a polycarboxylate dispersant to a solvent, stir and mix at a speed of 600 r / min to 800 r / min for 5 min to 10 min, then add the mixture A, stir and mix at a speed of 600 r / min to 800 r / min for 20 min to 40 min, then ultrasonically disperse at 40 kHz to 60 kHz for 15 min to 25 min, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 300 r / min to 500 r / min for 20 min to 30 min to obtain a mixture B;

[0022] S2: Add mixed material B, silane coupling agent KH-560, isopentyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer and phosphate plasticizer to the polyurethane resin in sequence under stirring at a speed of 200 r / min to 300 r / min, and continue stirring at a speed of 200 r / min to 300 r / min for 20 min to 40 min; filter through a sieve to obtain a coating.

[0023] In S2 of the above preparation method, the mesh size of the sieve is 200-250 meshes.

[0024] The invention provides a military stealth coating and a preparation method thereof, and the beneficial effects are as follows:

[0025] 1. The modified Fe3O4@ZIF-8 is added to the coating of the present invention. Fe3O4 itself is magnetic and can absorb radar waves through magnetic loss. ZIF-8 has a large specific surface area and a porous structure, which causes radar waves to be reflected and scattered multiple times in the pores, attenuating electromagnetic waves and forming a magnetic-dielectric synergistic wave absorption effect. After modification, aminopropyltriethoxysilane changes the surface properties of the material, better combines with other components, forms a more uniform structure, and enhances the absorption and scattering of radar waves. The infrared absorption characteristics of Fe3O4 and the low thermal conductivity of ZIF-8 reduce infrared radiation, and the nanostructure of Fe3O4 reduces infrared characteristics through thermal radiation regulation. After modification, the compatibility with the matrix is ​​improved, the distribution is more uniform, and heat transfer can be blocked more effectively, reducing the target infrared radiation intensity. The porous ZIF-8 and magnetic Fe3O4 scatter and absorb the laser. The modification increases the surface active sites, causing the laser to be scattered and absorbed multiple times inside the material, reducing the laser reflectivity. Aminopropyltriethoxysilane forms a protective film on the surface of Fe3O4@ZIF-8, isolating external corrosive substances, reducing contact with air and moisture, and improving chemical stability. Good chemical stability and good combination with other components enable the material to maintain stable performance in different environments, not easy to fall off or decompose, and extend its service life.

[0026] Second, manganese aluminum boron MAB phase ceramic material is added to the coating of the present invention, which has a special crystal structure and electromagnetic properties, adjusts electromagnetic parameters such as dielectric constant, better matches the electromagnetic properties of free space, reduces radar wave reflection, and achieves better absorption in some frequency bands. The high conductivity of MAB phase ceramics can induce eddy current loss, and its layered structure enhances the electromagnetic wave absorption bandwidth through interface polarization. It has a low infrared emissivity, can reduce its own infrared radiation, and to a certain extent adjusts the thermal conductivity of the material, so that the target surface temperature distribution is more uniform, reducing the probability of infrared detection. It has a certain absorption and scattering ability for lasers, and its crystal structure and chemical bond vibration can interact with laser energy and convert laser energy into other forms of energy dissipation. MAB phase ceramic materials have high chemical bond energy, stable structure, and are not easy to react with chemical substances such as acids and alkalis, and can maintain performance in complex chemical environments. With high hardness, wear resistance and chemical stability, it resists erosion and wear of the external environment during long-term use, maintains stealth performance, and extends the service life of the coating.

[0027] 3. Isoamyl p-methoxycinnamate is added to the coating of the present invention. Isoamyl p-methoxycinnamate has a specific molecular structure and functional group, and absorbs infrared light of a specific wavelength. It works in coordination with other ingredients to fill certain deficiencies in other materials such as performance and homogeneity, thereby synergistically improving the overall effect. Isoamyl p-methoxycinnamate has the ability to absorb ultraviolet rays, reduce the damage of ultraviolet rays to other ingredients in the coating, improve the light stability of the coating, prevent the coating from aging, discoloration, cracking, etc. due to long-term light exposure, and help maintain the appearance and performance stability of the stealth coating. The substance has certain organic properties, which helps to improve the film-forming properties of the coating, so that the coating forms a more uniform and smooth film layer on the surface of the object, which is conducive to reducing the optical scattering of the film surface to a certain extent, and has a certain auxiliary effect on the overall performance of the stealth coating. It can adjust the surface tension of the coating, so that the coating can be better spread and adhered on the surface of the object, improve the adhesion between the coating and the coated object, and ensure that the stealth coating can be firmly attached to the surface of the target object and play a role for a long time.

[0028] 4. Effect of using modified Fe3O4@ZIF-8 and isoamyl p-methoxycinnamate together: modified Fe3O4@ZIF-8 absorbs scattered radar waves, and isoamyl p-methoxycinnamate adjusts the electromagnetic properties of the coating surface. After the two are combined, the electromagnetic parameters of the coating surface are more optimized, and the radar wave absorption and scattering effects are enhanced. Modified Fe3O4@ZIF-8 blocks heat, and isoamyl p-methoxycinnamate absorbs specific infrared light. The two work together to make the infrared absorption and heat insulation effects more significant and reduce infrared radiation. Modified Fe3O4@ZIF-8 scatters and absorbs lasers, and isoamyl p-methoxycinnamate improves the optical properties of the coating surface, making the scattering and absorption of lasers on the surface and inside of the coating more sufficient, reducing laser reflection. The protective film of modified Fe3O4@ZIF-8 and the low surface energy of isoamyl p-methoxycinnamate jointly reduce the contact between external substances and the coating and improve chemical stability. The stealth performance is improved in many aspects, the performance degradation caused by the influence of the external environment is reduced, and the service life is extended.

[0029] 5. Advantages of modified Fe3O4@ZIF-8 over unmodified Fe3O4@ZIF-8: After modification, it is more tightly combined with other components and dispersed more evenly in the coating, improving overall performance. Chemical stability is enhanced, making it less susceptible to corrosion and degradation in harsh environments, maintaining stealth performance. In terms of radar, infrared, and laser stealth, due to changes in surface properties and better synergy with other components, it can more effectively absorb and scatter waves in the corresponding bands, resulting in better stealth effects.

[0030] Sixth, the preparation method of the present invention is designed to mix in steps, so that each component can be fully mixed and dispersed at different stages. For example, carbon nanotubes are premixed first and then gradually mixed with other components, which is more uniform than direct blending. The polycarboxylate dispersant is fully dispersed in the solvent in steps and then mixed with other components, which is conducive to the dispersant to play a role, and the components have more sufficient time for physical and chemical reactions, such as silane coupling agents can better achieve coupling effects. The coating structure formed is more stable, the performance reproducibility is good, and the performance fluctuations caused by uneven mixing and insufficient reaction are reduced.

[0031] 7. Carbon nanotubes have high conductivity and special structure, which can adjust electromagnetic parameters to absorb radar waves; they have good thermal conductivity, can assist heat dissipation and adjust infrared radiation; they can enhance the mechanical properties of the coating and improve its service life. Nano zinc oxide and nano titanium dioxide absorb and scatter ultraviolet rays, enhance chemical stability; they have certain absorption and scattering effects on infrared light, assist infrared stealth; improve the surface properties of the coating and improve weather resistance. Polyurethane resin is a film-forming substance, which provides good adhesion and flexibility, forms a continuous and stable coating, ensures that other components play a role, and improves service life. Isocyanate crosslinkers react with polyurethane resins to form a crosslinked structure, improve the hardness, strength and chemical stability of the coating, and extend its service life. Alkynediols wetting agents are used to reduce the surface tension of the coating, so that the coating can better wet the substrate, improve adhesion, and improve film quality. Phosphate plasticizers are used to increase the flexibility and plasticity of the coating, reduce the brittleness of the coating, and improve its service life. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0033] Example 1

[0034] A military stealth coating, the coating comprising the following raw materials in parts by mass: 5 parts of modified Fe3O4@ZIF-8, 13 parts of manganese aluminum boron MAB phase ceramic material, 7 parts of carbon nanotubes, 2.5 parts of nano zinc oxide, 2.5 parts of nano titanium dioxide, 2.5 parts of isopentyl p-methoxycinnamate, 3.5 parts of silane coupling agent KH-560, 55 parts of polyurethane resin, 1.2 parts of polycarboxylate dispersant and 7 parts of isocyanate crosslinking agent, 0.8 parts of acetylene glycol wetting agent, 0.3 parts of silicone defoaming agent, 4 parts of phosphate plasticizer and 40 parts of solvent; the solvent comprises the following raw materials in parts by mass: 45 parts of deionized water, 30 parts of propylene glycol methyl ether, 20 parts of propylene glycol methyl ether acetate and 18 parts of dipropylene glycol dimethyl ether.

[0035] Among them, the preparation method of modified Fe3O4@ZIF-8 includes the following steps: according to the mass ratio, Fe3O4@ZI F-8:aminopropyltriethoxysilane=100:3.5, Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 7 times that of Fe3O4@ZIF-8 at 50kHz until it is uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the reaction is stirred at 300r / min at 70°C for 4h, centrifuged at 9000r / min for 20min, the supernatant is discarded, and the precipitate is washed once with toluene with a mass of 2.2 times that of the precipitate, and then washed twice with ethanol with a mass of 2.2 times that of the precipitate, and then dried in a vacuum drying oven at 60°C for 14h and broken up to obtain Fe3O4@ZIF-8 surface modified by aminopropyltriethoxysilane, that is, modified Fe3O4@ZIF-8.

[0036] The preparation method of the above-mentioned military stealth coating comprises the following steps:

[0037] S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain mixture A; add polycarboxylate dispersant to the solvent, stir and mix at a speed of 700 r / min for 8 minutes, then add mixture A, stir and mix at a speed of 700 r / min for 30 minutes, then disperse ultrasonically at 50 kHz for 20 minutes, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 400 r / min for 25 minutes to obtain mixture B;

[0038] S2: Under stirring at a speed of 250 r / min, add mixed material B, silane coupling agent KH-560, isopentyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer, and phosphate plasticizer to the polyurethane resin in sequence, and continue stirring at a speed of 250 r / min for 30 minutes; filter through a 200-mesh sieve to obtain a coating.

[0039] Example 2

[0040] A military stealth coating comprises the following raw materials in parts by mass: 4 parts of modified Fe3O4@ZIF-8, 12 parts of manganese aluminum boron MAB phase ceramic material, 6 parts of carbon nanotubes, 2 parts of nano zinc oxide, 2 parts of nano titanium dioxide, 2 parts of isopentyl p-methoxycinnamate, 3 parts of silane coupling agent KH-560, 50 parts of polyurethane resin, 1 part of polycarboxylate dispersant and 6 parts of isocyanate crosslinking agent, 0.5 parts of acetylene glycol wetting agent, 0.2 parts of silicone defoaming agent, 3 parts of phosphate plasticizer and 35 parts of solvent; the solvent comprises the following raw materials in parts by mass: 40 parts of deionized water, 20 parts of propylene glycol methyl ether, 10 parts of propylene glycol methyl ether acetate and 10 parts of dipropylene glycol dimethyl ether.

[0041] Among them, the preparation method of modified Fe3O4@ZIF-8 includes the following steps: according to the mass ratio, Fe3O4@ZI F-8:aminopropyltriethoxysilane=100:2, Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 6 times that of Fe3O4@ZIF-8 at 40kHz until it is uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the reaction is stirred at 200r / min at 60°C for 3h, centrifuged at 8000r / min for 15min, the supernatant is discarded, and the precipitate is washed once with toluene with a mass of 1.8 times that of the precipitate, and then washed twice with ethanol with a mass of 1.8 times that of the precipitate, and then dried in a vacuum drying oven at 55°C for 12h and broken up to obtain Fe3O4@ZIF-8 surface modified by aminopropyltriethoxysilane, that is, modified Fe3O4@ZIF-8.

[0042] The preparation method of the above-mentioned military stealth coating comprises the following steps:

[0043] S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain mixture A; add polycarboxylate dispersant to the solvent, stir and mix at a speed of 600 r / min for 5 minutes, then add mixture A, stir and mix at a speed of 600 r / min for 20 minutes, then disperse ultrasonically at 40 kHz for 15 minutes, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 300 r / min for 20 minutes to obtain mixture B;

[0044] S2: Under stirring at 200 r / min, add mixed material B, silane coupling agent KH-560, isoamyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer, and phosphate plasticizer to the polyurethane resin in sequence, and continue stirring at 200 r / min for 20 minutes; filter through a 200-mesh sieve to obtain a coating.

[0045] Example 3

[0046] A military stealth coating, the coating comprising the following raw materials in parts by mass: 4 parts of modified Fe3O4@ZIF-8, 15 parts of manganese aluminum boron MAB phase ceramic material, 6 parts of carbon nanotubes, 3 parts of nano zinc oxide, 2 parts of nano titanium dioxide, 3 parts of isopentyl p-methoxycinnamate, 3 parts of silane coupling agent KH-560, 60 parts of polyurethane resin, 1 part of polycarboxylate dispersant and 8 parts of isocyanate crosslinking agent, 0.5 parts of acetylene glycol wetting agent, 0.5 parts of silicone defoaming agent, 3 parts of phosphate plasticizer and 42 parts of solvent; the solvent comprises the following raw materials in parts by mass: 40 parts of deionized water, 40 parts of propylene glycol methyl ether, 10 parts of propylene glycol methyl ether acetate and 25 parts of dipropylene glycol dimethyl ether.

[0047] Among them, the preparation method of modified Fe3O4@ZIF-8 includes the following steps: according to the mass ratio, Fe3O4@ZI F-8:aminopropyltriethoxysilane=100:2.5, Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 8 times that of Fe3O4@ZIF-8 at 45kHz until it is uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the reaction is stirred at 400r / min at 60°C for 3h, centrifuged at 10000r / min for 15min, the supernatant is discarded, and the precipitate is washed once with toluene with a mass of 2.5 times that of the precipitate, and then washed twice with ethanol with a mass of 2.5 times that of the precipitate, and then dried in a vacuum drying oven at 65°C for 12h and broken up to obtain Fe3O4@ZIF-8 surface modified by aminopropyltriethoxysilane, that is, modified Fe3O4@ZIF-8.

[0048] The preparation method of the above-mentioned military stealth coating comprises the following steps:

[0049] S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain mixture A; add polycarboxylate dispersant to the solvent, stir and mix at a speed of 600 r / min for 10 min, then add mixture A, stir and mix at a speed of 600 r / min for 20 min, then disperse ultrasonically at 60 kHz for 15 min, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 500 r / min for 20 min to obtain mixture B;

[0050] S2: Under stirring at 200 r / min, add mixed material B, silane coupling agent KH-560, isopentyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer, and phosphate plasticizer to the polyurethane resin in sequence, and continue stirring at 200 r / min for 40 min; filter through a 200-mesh sieve to obtain a coating.

[0051] Example 4

[0052] A military stealth coating, the coating comprising the following raw materials in parts by mass: 6 parts of modified Fe3O4@ZIF-8, 15 parts of manganese aluminum boron MAB phase ceramic material, 8 parts of carbon nanotubes, 3 parts of nano zinc oxide, 3 parts of nano titanium dioxide, 3 parts of isopentyl p-methoxycinnamate, 4 parts of silane coupling agent KH-560, 60 parts of polyurethane resin, 1.5 parts of polycarboxylate dispersant and 8 parts of isocyanate crosslinking agent, 1 part of acetylene glycol wetting agent, 0.5 parts of silicone defoaming agent, 5 parts of phosphate plasticizer and 45 parts of solvent; the solvent comprises the following raw materials in parts by mass: 50 parts of deionized water, 40 parts of propylene glycol methyl ether, 30 parts of propylene glycol methyl ether acetate and 25 parts of dipropylene glycol dimethyl ether.

[0053] Among them, the preparation method of modified Fe3O4@ZIF-8 includes the following steps: according to the mass ratio, Fe3O4@ZI F-8:aminopropyltriethoxysilane=100:5, Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 8 times that of Fe3O4@ZIF-8 at 60kHz until it is uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the reaction is stirred at 400r / min at 80°C for 5h, centrifuged at 10000r / min for 25min, the supernatant is discarded, and the precipitate is washed twice with toluene with a mass of 2.5 times that of the precipitate, and then washed three times with ethanol with a mass of 2.5 times that of the precipitate, and then dried in a vacuum drying oven at 65°C for 15h and broken up to obtain Fe3O4@ZIF-8 surface modified by aminopropyltriethoxysilane, that is, modified Fe3O4@ZIF-8.

[0054] The preparation method of the above-mentioned military stealth coating comprises the following steps:

[0055] S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain mixture A; add polycarboxylate dispersant to the solvent, stir and mix at a speed of 800 r / min for 10 min, then add mixture A, stir and mix at a speed of 800 r / min for 40 min, then disperse ultrasonically at 60 kHz for 25 min, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 500 r / min for 30 min to obtain mixture B;

[0056] S2: Under stirring at a speed of 300 r / min, add mixed material B, silane coupling agent KH-560, isopentyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer, and phosphate plasticizer to the polyurethane resin in sequence, and continue stirring at a speed of 300 r / min for 40 minutes; filter through a 250-mesh sieve to obtain a coating.

[0057] Example 5

[0058] A military stealth coating, the coating comprising the following raw materials in parts by mass: 6 parts of modified Fe3O4@ZIF-8, 12 parts of manganese aluminum boron MAB phase ceramic material, 8 parts of carbon nanotubes, 2 parts of nano zinc oxide, 3 parts of nano titanium dioxide, 2 parts of isopentyl p-methoxycinnamate, 4 parts of silane coupling agent KH-560, 50 parts of polyurethane resin, 1.5 parts of polycarboxylate dispersant and 6 parts of isocyanate crosslinking agent, 1 part of acetylene glycol wetting agent, 0.2 parts of silicone defoaming agent, 5 parts of phosphate plasticizer and 38 parts of solvent; the solvent comprises the following raw materials in parts by mass: 50 parts of deionized water, 20 parts of propylene glycol methyl ether, 30 parts of propylene glycol methyl ether acetate and 10 parts of dipropylene glycol dimethyl ether.

[0059] Among them, the preparation method of modified Fe3O4@ZIF-8 includes the following steps: according to the mass ratio, Fe3O4@ZI F-8:aminopropyltriethoxysilane=100:4.5, Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 6 times that of Fe3O4@ZIF-8 at 55kHz until it is uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the reaction is stirred at 200r / min at 80°C for 5h, centrifuged at 8000r / min for 25min, the supernatant is discarded, and the precipitate is washed twice with toluene with a mass of 1.8 times that of the precipitate, and then washed three times with ethanol with a mass of 1.8 times that of the precipitate, and then dried in a vacuum drying oven at 55°C for 15h and broken up to obtain Fe3O4@ZIF-8 surface modified by aminopropyltriethoxysilane, that is, modified Fe3O4@ZIF-8.

[0060] The preparation method of the above-mentioned military stealth coating comprises the following steps:

[0061] S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain mixture A; add polycarboxylate dispersant to the solvent, stir and mix at a speed of 800 r / min for 5 minutes, then add mixture A, stir and mix at a speed of 800 r / min for 40 minutes, then disperse ultrasonically at 40 kHz for 25 minutes, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 300 r / min for 30 minutes to obtain mixture B;

[0062] S2: Under stirring at 300 r / min, add mixed material B, silane coupling agent KH-560, isopentyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer and phosphate plasticizer to the polyurethane resin in sequence, and continue stirring at 300 r / min for 20 min; filter through a 250-mesh sieve to obtain a coating.

[0063] In the above embodiments, the particle size range of Fe3O4@ZIF-8 is 150nm to 400nm. The sheet diameter range of manganese aluminum boron MA B phase ceramic material is 5μm to 50μm. The particle size range of carbon nanotubes is below 30nm. The particle size range of nano zinc oxide is below 30nm. The particle size range of nano titanium dioxide is below 50nm.

[0064] In the above embodiments, the sources of raw materials: Fe3O4@ZIF-8 comes from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., numbered XFF58. Manganese aluminum boron MAB phase ceramic material comes from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., Mn2AlB2 manganese aluminum boron MAB phase ceramic material, numbered XFK49. Isoamyl p-methoxycinnamate comes from Shanghai Aoji Chemical Co., Ltd. Silane coupling agent KH-560 (propyl trimethoxysilane) comes from Dongguan Kangjin New Materials Technology Co., Ltd. Polyurethane resin comes from Dongguan Yibao Resin Co., Ltd., model BY-40. Polycarboxylate dispersant comes from Shandong Yousuo Chemical Technology Co., Ltd., model 5040. Isocyanate crosslinker comes from Shanghai Youen Chemical Co., Ltd., model 074. Alkyne diol wetting agent comes from Anhui Yuanchen New Materials Technology Co., Ltd., model YC-3003. Silicone defoamer comes from Guangdong Yuanfeng New Materials Co., Ltd., Dow Corning AFE-3168 silicone defoamer. Phosphate plasticizers were sourced from Shanghai Zhenzhun Biotechnology Co., Ltd., tricresyl phosphate (TCP). Aminopropyl triethoxysilane was sourced from Dongguan Kangjin New Materials Technology Co., Ltd., model KH-550. Propylene glycol methyl ether (PM) was sourced from Shandong Mingcheng New Materials Co., Ltd. Propylene glycol methyl ether acetate (PMA) was sourced from Zhongrun (Shandong) New Materials Co., Ltd., and dipropylene glycol dimethyl ether (DMM) was sourced from Guangzhou Changhong Chemical Technology Co., Ltd.

[0065] Comparative Example 1

[0066] No modified Fe3O4@ZIF-8 was added to the coating; other parameters and methods were the same as in Example 1.

[0067] Comparative Example 2

[0068] In the coating, the modified Fe3O4@ZIF-8 is replaced by Fe3O4@ZIF-8; other parameters and methods are the same as in Example 1.

[0069] Comparative Example 3

[0070] In the coating, the manganese aluminum boron MAB phase ceramic material is replaced by alumina ceramic; other parameters and methods are the same as in Example 1.

[0071] Comparative Example 4

[0072] In the coating, isoamyl p-methoxycinnamate is not added; the mass fraction of isoamyl p-methoxycinnamate is replaced by a solvent; other parameters and methods are the same as in Example 1.

[0073] Comparative Example 5

[0074] In the coating, the modified Fe3O4@ZIF-8 is replaced by Fe3O4@ZIF-8; isoamyl p-methoxycinnamate is not added; the mass fraction of isoamyl p-methoxycinnamate is replaced by a solvent; other parameters and methods are the same as in Example 1.

[0075] Comparative Example 6

[0076] The preparation method is to directly blend all raw materials without preparing mixed material B in advance to obtain the coating; other parameters and methods are the same as those in Example 1.

[0077] The coatings prepared in the above-mentioned embodiments and comparative examples were tested for their performance.

[0078] The coating was applied on a tent fabric (polyester fabric) with a thickness of 0.5 mm to prepare a test sample.

[0079] 1. Radar stealth performance test: Carefully cut the coated tent fabric into 1.5m×1.5m square samples to ensure neat edges. Use a clamp to fix the sample flat on a high-strength test stand to ensure that the sample is wrinkle-free and shake-free during the test. Use a high-performance vector network analyzer to set the transmission frequency range to 0.3GHz-20GHz and the frequency scan step to 0.05GHz to obtain more accurate RCS data. The transmission power is set to 15dBm to ensure that the signal strength can effectively detect the sample without causing damage to the sample. The transmitting antenna and the receiving antenna are located on both sides of the turntable, forming a 45° angle with the sample, and the antenna is 5m away from the sample. The turntable rotates at a constant speed of 1° / s to simulate the situation where the target is detected by radar at different angles. During the rotation process, the vector network analyzer records the RCS values ​​of the sample at different frequencies and angles in real time. To ensure data accuracy, each sample is tested 3 times, and the average value is finally taken as the radar stealth performance index of the sample. The test results are shown in Table 1 below.

[0080] 2. Infrared stealth performance test: Place the sample in a constant temperature and humidity environment at 25°C and 50% relative humidity for 2 hours to allow the sample to fully reach a thermal equilibrium state and eliminate the impact of environmental factors on the test results. Use an infrared thermal imager to shoot at a distance of 1m from the sample, ensuring that the thermal imager lens is vertically aligned with the center of the sample. The resolution of the thermal imager is set to 640×480, which can clearly capture subtle temperature differences on the surface of the sample. Emissivity measurement: Use a Fourier transform infrared spectrometer to measure the infrared emissivity of the sample in the 8μm-14μm band. Set the number of scans to 64 times. The resolution is set to 2cm -1 , which can accurately distinguish the emissivity changes of the sample in this band. Three different positions are selected for each sample for measurement, and the average value is taken as the infrared emissivity index of the sample. The test results are shown in Table 1 below.

[0081] 3. Laser stealth performance test: Fix the sample on an electric bracket with precise angle adjustment to ensure that the sample is stable during the test and the angle can be easily adjusted. A pulsed laser with a wavelength of 1.06μm is used as the light source, which is a common laser detection wavelength. The transmission power is set to 10W, the pulse width is 10ns, and the repetition frequency is 10Hz to simulate a real laser detection scene. The receiving device is located 1m in front of the sample and is equipped with a high-precision photoelectric detector that can accurately receive the reflected laser signal. Adjust the angle between the laser and the sample to 30°, and measure the reflectivity of the sample to the laser. Each sample is measured 5 times, and the average value of the 5 measurements is taken as the laser reflectivity index of the sample. The test results are shown in Table 1 below.

[0082] 4. Chemical stability test: Place the sample in a climate simulation box to simulate a high temperature and high humidity environment. The temperature is set to 60°C and the relative humidity is 90%. The duration is 1000 hours, simulating the long-term use of tents in tropical humid areas. Take out the sample after 1000 hours and retest the performance: Use the previous radar, infrared and laser stealth performance test equipment again to measure the stealth performance value of the sample, compare it with the initial value, and calculate the performance reduction rate; take the average value of the radar, infrared and laser stealth performance reduction rate to evaluate the impact of chemical stability on stealth performance. The test results are shown in Table 1 below.

[0083] 5. Service life test: Install the sample on the wear tester and set the friction pressure to 500g to simulate the friction force in actual use. The friction frequency is 100 times / minute to accelerate the wear rate. At the same time, simulate ultraviolet radiation with a power of 100W / m 2 The UV lamp is set at a distance of 30cm from the sample to simulate outdoor sunlight. The rain spray rate is set to 1L / min to simulate a rainy day environment. Sample inspection: Stop the test every 50 hours and carefully inspect the sample surface. When the average stealth performance decreases by more than 30%, record the test time at this time as the service life of the sample. The test results are shown in Table 1 below.

[0084] Table 1 Test results

[0085]

[0086] From the above results, it can be seen that Examples 1 to 5 have a complete and optimized formula system, and the synergistic stealth effect of each component is significant. The components interact with each other to form a stable chemical structure, which has strong resistance to environmental corrosion, and the proportion of stealth performance degradation after 1000 hours is relatively low.

[0087] In comparative example 1, modified Fe3O4@ZIF-8 was not added, and the key wave-absorbing component was missing, resulting in a significant decrease in radar stealth performance. In terms of infrared and laser stealth, the performance was also seriously affected due to the lack of the component's regulating effect on the overall electromagnetic properties. In the simulated environment, the lack of the stabilizing effect of the component caused the coating to have poor overall performance and could not effectively resist wear and environmental erosion.

[0088] In Comparative Example 2, unmodified Fe3O4@ZIF-8 was used instead, and the performance was not as good as that of the embodiment. The unmodified material has poor synergy with other components and cannot fully play the role of absorbing waves and adjusting electromagnetic properties. The radar, infrared, and laser stealth performance are reduced. The chemical stability is affected, and the stability of the unmodified material in the environment is poor, because the decline in the overall performance of the coating makes it more likely to fail in the accelerated aging test.

[0089] In comparative example 3, alumina ceramics are used to replace manganese aluminum boron MAB phase ceramic materials. Due to the different electromagnetic and infrared characteristics of the two, the stealth performance is deteriorated. The wave absorption and scattering characteristics of alumina ceramics are not as good as those of manganese aluminum boron MAB phase ceramic materials. The average radar RCS is 0.9m 2 , infrared emissivity is 0.45, laser reflectivity is 0.35. Chemical stability is also affected, the bonding and synergy between alumina ceramics and other components are not as good as manganese aluminum boron MAB phase ceramic materials, because the change in material properties affects the overall wear resistance and weather resistance of the coating.

[0090] In comparative example 4, isoamyl p-methoxycinnamate was not added, and the stealth performance was reduced. This component contributes to multi-band stealth, and its absence affects the coating's ability to absorb and scatter electromagnetic waves in different bands. This component also has a certain synergistic effect on the chemical stability and durability of the coating.

[0091] In Comparative Example 5, there are problems of unmodified Fe3O4@ZIF-8 and lack of isoamyl p-methoxycinnamate, and the stealth performance and chemical stability are worse.

[0092] In Comparative Example 6, the mixture B was not prepared in advance, but directly blended, resulting in uneven dispersion of the components, which affected the combination of the coating and the fabric and the synergistic effect of the components. The chemical stability was affected, indicating that the uneven components led to a decrease in the coating's ability to resist environmental erosion. Because the components were unevenly dispersed, the coating was more likely to fall off and its performance deteriorated in the accelerated aging test.

Claims

1. A military stealth coating, characterized in that: The coating comprises the following raw materials in parts by weight: 4 to 6 parts of modified Fe3O4@ZIF-8, 12 to 15 parts of manganese aluminum boron MAB phase ceramic material, 6 to 8 parts of carbon nanotubes, 2 to 3 parts of nano zinc oxide, 2 to 3 parts of nano titanium dioxide, 2 to 3 parts of isopentyl p-methoxycinnamate, 3 to 4 parts of silane coupling agent KH-560, 50 to 60 parts of polyurethane resin, 1 to 1.5 parts of polycarboxylate dispersant and 6 to 8 parts of isocyanate crosslinking agent, 0.5 to 1 part of acetylene glycol wetting agent, 0.2 to 0.5 parts of silicone defoaming agent, 3 to 5 parts of phosphate plasticizer and 35 to 45 parts of solvent; The modified Fe3O4@ZIF-8 is Fe3O4@ZIF-8 surface-modified by aminopropyltriethoxysilane.

2. A military stealth coating according to claim 1, characterized in that: The preparation method of the modified Fe3O4@ZIF-8 comprises the following steps: according to the mass ratio of Fe3O4@ZIF-8:aminopropyltriethoxysilane=100:(2-5), Fe3O4@ZIF-8 is ultrasonically dispersed in toluene with a mass of 6 to 8 times of Fe3O4@ZIF-8 at 40kHz to 60kHz until uniform, then aminopropyltriethoxysilane is added, and under nitrogen protection, the mixture is stirred at 60°C to 80°C and a speed of 200r / min to 400r / min for reaction for 3h The mixture was centrifuged at 8000 r / min to 10000 r / min for 15 to 25 min, the supernatant was discarded, the precipitate was washed 1 to 2 times with toluene (1.8 to 2.5 times the mass of the precipitate), and then washed 2 to 3 times with ethanol (1.8 to 2.5 times the mass of the precipitate), and then dried in a vacuum drying oven at 55 to 65 ° C for 12 to 15 h, and broken up to obtain Fe3O4@ZIF-8 surface-modified with aminopropyltriethoxysilane, i.e., modified Fe3O4@ZIF-8.

3. A military stealth coating according to claim 2, characterized in that: The particle size of the Fe3O4@ZI F-8 is in the range of 150nm to 400nm.

4. The military stealth coating according to claim 1, characterized in that: The solvent comprises the following raw materials in parts by mass: 40 to 50 parts of deionized water, 20 to 40 parts of propylene glycol methyl ether, 10 to 30 parts of propylene glycol methyl ether acetate and 10 to 25 parts of dipropylene glycol dimethyl ether.

5. The military stealth coating according to claim 1, characterized in that: The sheet diameter of the manganese aluminum boron MA B phase ceramic material ranges from 5 μm to 50 μm.

6. The military stealth coating according to claim 1, characterized in that: The particle size of the carbon nanotubes is below 30 nm.

7. The military stealth coating according to claim 1, characterized in that: The particle size range of the nano zinc oxide is below 30 nm.

8. The military stealth coating according to claim 1, characterized in that: The particle size range of the nano titanium dioxide is below 50 nm.

9. A method for preparing a military stealth coating, used for preparing a military stealth coating as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: Premix carbon nanotubes, nano zinc oxide and nano titanium dioxide by air flow according to their mass fractions to obtain a mixture A; add a polycarboxylate dispersant to a solvent, stir and mix at a speed of 600 r / min to 800 r / min for 5 min to 10 min, then add the mixture A, stir and mix at a speed of 600 r / min to 800 r / min for 20 min to 40 min, then ultrasonically disperse at 40 kHz to 60 kHz for 15 min to 25 min, then add manganese aluminum boron MAB phase ceramic material and modified Fe3O4@ZIF-8, stir and mix at a speed of 300 r / min to 500 r / min for 20 min to 30 min to obtain a mixture B; S2: Add mixed material B, silane coupling agent KH-560, isopentyl p-methoxycinnamate, isocyanate crosslinking agent, acetylene glycol wetting agent, silicone defoamer and phosphate plasticizer to the polyurethane resin in sequence under stirring at a speed of 200 r / min to 300 r / min, and continue stirring at a speed of 200 r / min to 300 r / min for 20 min to 40 min; filter through a sieve to obtain a coating.

10. The method for preparing a military stealth coating according to claim 9, characterized in that: In S2, the mesh size of the sieve is 200-250 meshes.

Citation Information

Patent Citations

  • Method for preparing water-based infrared-laser composite stealthy coating

    CN102925050A

  • Hyperspectral infrared camouflage coating and application thereof

    CN116043572A

  • Infrared coating compatible with radar stealth, and method for preparing same

    WO2019001104A1